Peran Pendidikan Agama Islam Dalam Pembentukan Karakter Sosial Dalam Bermasyarakat - Khurin In'Ratnasari; Yovita Dyah Permatasari; Mar’atus Sholihah (FALASIFA : Jurnal Studi Keislaman, 2020)
Islamic religious education is very important for shaping character, especially in social society. In today's era, students tend not to care about society, therefore forming a good character is very important, especially in the social community in Islamic religious education itself, it teaches us that we are required to have good character as taught by the Prophet Muhammad; Allah SWT said, which means "and indeed you (Muhammad) have a noble character". Because of this, it can be concluded that the Prophet Muhammad, was sent to earth to improve the character of all human beings. Thus, the character of education from an Islamic point of view is needed, especially in Islamic educational institutions. So, from various problems related to morals which are ideally able to realize character education, especially in social society in an Islamic perspective in the form of mutual care. courtesy to parents. sense of responsibility and care for fellow human beings.